BMI and Odds of Endometrial Adenocarcinoma in Czech Women - a Case Control Study - Tichý, Michal; Ptáčková, Hana; Plančíková, Dominika; Majdan, Marek; Chodacká, Martina (Klinicka onkologie, 2019)
INTRODUCTION: The incidence of malignant tumors of the uterine body is increasing in the Czech Republic. Endometrial adenocarcinoma is one of the most frequent morphological types. Obesity or even overweight is a risk factor for the development of this disease. More accurate stratification of risk relative to body mass index (BMI) has not yet been determined in the Czech Republic, although the risk of overweight (BMI 25-29.9) has been reported in one study as comparable to that of first or second degree obesity (BMI 30-30.9). PATIENTS AND METHODS: The study population included 376 women of Caucasian race diagnosed with endometrial adenocarcinoma, with BMI measured simultaneously, in 2005-2017. A control group consisted of an equal number of age-matched women not diagnosed with any oncological or gynecological disease. These two files were statistically processed. RESULTS: Odds (OR, 95% CI) relative to normal weight women, overweight women were at 2.26-times higher odds of endometrial adenocarcinoma, and women with obesity were at 5.18-8.67-, and 24.70-times higher odds, depending on the severity of obesity. CONCLUSION: The hypothesis that overweight represents same risk for the development of endometrial adenocarcinoma, as lower degrees of obesity was not verified. However overweight is serious risk for endometrial adenocarcinoma development. The odds of endometrial adenocarcinoma is correlated with increasing BMI and in the population studied is higher than reported previously for all endometrial carcinoma subtypes. This work was carried out with the support of an internal grant of Krajská zdravotní, a.s., for the years 2017-2019: IGA217129002. The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 29. 4. 2019 Accepted: 22. 7. 2019.
Keywords: endometrial (endometrioid) adenocarcinoma; obezita; Adenocarcinoma; Humans; Case-Control Studies; index tělesné hmotnosti; Body Mass Index; Overweight; odds; studie případů a kontrol; Female; overweight; Endometrial Neoplasms; endometrial (endometrioid) carcinoma; lidé; czech women; ženské pohlaví; Czech Republic; Odds Ratio; obesis; nádory endometria; adenokarcinom; Obesity; Česká republika; odds ratio; nadváha